Pricing a combined life and health insurance with level premiums and varying benefits - Kabiri, Azra May B.; Cuaresma, Diane Carmeliza N.; Mamplata, Jonatahn B. (Vol.150, No.4 (August 2021) pages 691-702.)
"The growing interest in insurance poses a threat to insurance companies. As the number of individuals seeking insurance coverage increases, the number of individuals adversely selecting the insurer also increases, which can lead to the insurance product being unprofitable. Thus, this study explores designing an insurance product that will reflect the actual claims of an individual to his/her policy- that will hopefully help prevent unprofitability of the insurance product"-Title page.